Preparation of a poly(3-hexylthiophene)-grafted indium tin oxide/poly(3-hexylthiopene) composite and its conductivity-temperature characteristics - Liu, Chuanjun; Oshima, Kenji; Shimomura, Masato; Miyauchi, Shinnosuke (Journal of Applied Polymer Science, 2006)
The temperature–conductivity characteristics of poly(3‐hexylthiophene) (P3HT) composites filled with P3HT‐grafted indium tin oxide (ITO) particles were investigated in this work. The ITO particles were first treated with a silane coupling reagent of 3‐aminopropyltriethoxysilane (APS), and then thiophene rings were introduced through a condensation reaction between the ending amino groups of APS and the carboxylic groups of thiophene‐3‐acetic acid. The composites were prepared by the polymerization filling of the 3‐hexylthiophene (3HT) monomer with the thiophene‐ring‐introduced ITO particles. Elemental analysis, Fourier transform infrared, and X‐ray photoelectron spectroscopy were used to confirm the grafting reaction on the ITO surface. The longer the polymerization time was or the higher the 3HT/ITO feeding ratio was, the more P3HT was grafted. The influence of the grafted amount on the electrical properties of ITO particles was attributed to the wrapping effect formed by the grafted P3HT on the surface of the ITO particles. The conductivity change of the P3HT‐grafted ITO/P3HT composites was proved to be subject to the change in the average gap width of ITO interparticles, which was determined by the filling ratio of P3HT to ITO in the polymerization and the volume expansion effect of a P3HT thin film between neighboring ITO particles during the heating process. In comparison with the ungrafted ITO/P3HT composites, the grafting treatment enhanced the interaction between the particles and polymer matrix, and this was helpful for obtaining a more homogeneous dispersion structure for the composites and thus afforded a higher positive temperature coefficient intensity and better reproducibility. © 2006 Wiley Periodicals, Inc. J Appl Polym Sci 100: 1881–1888, 2006